The Homophobic Call-Outs of COVID-19: Spurring and Spreading Angry Attention From Girregi Journalism Online to YouTube in South Korea - Lee, Jin; Lee, Jeehyun Jenny (University of Southern California, 2023)
South Korea’s gay community received heightened public attention in May 2020 when a news agency reported that a COVID-19 patient had visited several gay clubs in the multicultural district Itaewon, Seoul. Following this announcement, a plethora of news content was published across various online media platforms. Through a case study of how the news on the Itaewon outbreak spread from online news to YouTube, we investigate the modalities of homophobic discourse and its circulation across different online media outlets. By examining the interplay between the Korean online news media (derogatorily called girregi journalism) and YouTube news channels in spreading the Itaewon story, we discuss how the nationwide homophobic call-outs against the gay community were instigated within an attention ecology. We argue that news media and YouTube news channels work together as affective mechanisms that define the dominant feeling rules about nonnormative subjects as a way of engaging with the pandemic crisis, through the accumulation of affect and attention toward gay bodies.